To travel, or not to travel? The impacts of travel constraints and perceived travel risk on travel intention among Malaysian tourists amid the COVID‐19. Issue 2 (15th November 2021) - Aziz, Norzalita Abd; Long, Fei
Abstract: The tourism and hospitality industry has been deeply disrupted by the COVID‐19 pandemic since its inception in December 2019. Many tourists are too anxious to travel. Thus, understanding how travel constraints and perceived travel risk influence travel intention is crucial for many destinations in their post‐crisis recovery. Drawing upon 357 Malaysian respondents, this study finds that structural constraints initiate tourists' negotiation process for travel decisions, which is inconsistent with the original Leisure Constraints Model. Nevertheless, it is reaffirmed that intrapersonal constraints remain the centrality of the negotiation process as they mediate the relationship between structural constraints, perceived travel risk and travel intention. These findings provide some theoretical contributions with regard to the Leisure Constraints Model and perceived travel risk in the context of the COVID‐19. Based on the theoretical contributions, this study also sheds light on tourism revival from a practical perspective. Tourism authorities, destination marketing organizations, and business operators are suggested to take measures to restore tourists' confidence toward travel by reducing structural constraints and mitigating tourists' risk perception in a cooperative manner.